2019
DOI: 10.29131/uiibd.570312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Accounting Professions’ Alienation From Work on Happiness at Workplace: A Research at Burdur Province and Bucak County

Abstract: International Journal of Economics and Administrative Sciences is peer reviewed journal published twice a year. It publishes articles both in Turkish and English languages in the fields of economics, business administration, international relations, political science and public administration, behavioral sciences, finance, econometrics, labor economics and industrial relations, banking and finance, human resources management, management information systems, social services, international trade and logistics, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For the organizations to sustain their existence, gain a competitive advantage and be successful in an intensely competitive environment, the performance and productivity of employees play an important role as well as the effective use of organizational resources. One of the important factors that enable employees to work with high performance and productivity is their degree of happiness at the workplace (Akın & Aktar, 2019). Employees' happiness at the workplace increases their well-being, productivity, performance, loyalty, creativity, and organizational success.…”
Section: Effect Of Ethical Leadership and Employee Voice On Happiness...mentioning
confidence: 99%
“…For the organizations to sustain their existence, gain a competitive advantage and be successful in an intensely competitive environment, the performance and productivity of employees play an important role as well as the effective use of organizational resources. One of the important factors that enable employees to work with high performance and productivity is their degree of happiness at the workplace (Akın & Aktar, 2019). Employees' happiness at the workplace increases their well-being, productivity, performance, loyalty, creativity, and organizational success.…”
Section: Effect Of Ethical Leadership and Employee Voice On Happiness...mentioning
confidence: 99%
“…Researchers have stated that workplace happiness not only improves employees' quality of life, but also has positive effects on their performance levels (Erer, 2021). A review of the literature reveals that numerous studies have suggested a positive relationship between workplace happiness and employee performance (Bockerman & Ilmakunnas, 2012;Akın & Aktar, 2019). It is also suggested that happy employees tend to be more productive and make more efforts to fulfill their job roles (Zelensky et al 2008) .…”
Section: The Relationship Between Workplace Happiness and Employeementioning
confidence: 99%